Risk factors and outcome of Hypernatremia amongst severe adult burn patients - Lam, N.N. (Ann Burns Fire Disasters, 2018)
A descriptive study was conducted on 135 adult severe burn patients treated at the Burn ICU, National Institute of Burns from 1/2017 to 12/2017. Hypernatremia was defined as increased plasma sodium ≥ 146 mmol/l. It was recorded in 24.4% of total patients with onset time of 8.3 ± 4.8 days, ranging from the 5th to 21st day postburn. Moderate and severe hypernatremia was recorded in 16 (54.5%) patients. Multivariate logistic analysis indicated that increased age, burn extent, mechanical ventilation and ventilation duration were independent predictive factors for the development of hypernatremia. Significantly higher mortality rate (59.5% vs. 40.5% respectively; p = .001) and longer duration of stay in the ICU (23.2 ± 15.4 days vs. 16.2 ± 11.6; p = .01) and in the hospital (74.4 ± 43.7 days vs. 37.9 ± 22.9; p = .002) were seen in the hypernatremia group compared to normonatremic patients. It is necessary to find further effective interventions for the prevention and treatment of this fatal complication among severe burn patients.